Safety Analysis of Helicopter Models using Hybrid Systems with Geometric Programming - Salmah, (2010)
Designing autonomous flight control system for a mini scale helicopter is very challenging due to their highly nonlinear and unstable behaviors. Unlike its full-size counterparts, the mathematical model of mini scale helicopter exhibits not only increased sensitivity to control inputs and disturbances but also higher bandwidth of its dynamics. One approach to control the nonlinear system is hybrid control technique which is predicated on the linearization in each mode to have a simple linear model. This leads to a switching problem because of changes from one mode to another mode in its flight envelope. This paper investigates safety analysis of helicopter model during mode transition using hybrid systems approach. In this case, it is is limited to two modes condition in the helicopter model, i.e. hover and cruise.